An empirical analysis on the impact of risk on customer loyalty in electronic commerce. (1st January 2011) - Ramanathan, Ramakrishnan
In this paper, we discuss a research study that explores the role of risk on the influence of various performance attributes on customer loyalty in the context of the electronic marketplace. We use data from online customer ratings of 532 e-commerce websites for the purpose. Seven attributes linked to various performance options available to managers of e-commerce websites are considered. Websites are grouped into risk and non-risk groups based on the nature of products sold. Empirical analysis is conducted using a combination of multivariate statistical techniques: multivariate analysis of variance (MANOVA), factor analysis and multiple regression. Our results show that online customer ratings differ significantly in terms of risk characteristics of the products sold for all the performance attributes, except for 'comparative prices'. Service-oriented attributes, pre-purchase attributes and post-purchase attributes are significant for both risk groups (risk and non-risk).